À mon âge je me cache encore pour fumer - Rayhana 1963-; Abbass, Hiam 1960-; Kaci, Nadia (ARTE France développement, 2017)
"In the heart of the hammam, far from the accusing gaze of men, mothers, lovers, virgins and Islamic fanatics, butts and burqas, mingle and mix, confront one another, with laughter, tears, rage, the Bible and the Koran... before the flash of a dagger and the silence of God."--UniFrance webiste
Original: Frankreich/Griechenland/Algerien 2016
Farbe, Bildformat 2.39:1 (16/9)
Keywords: Women / Algeria / Algiers / Social conditions / Drama; Baths, Turkish / Drama; Baths, Turkish; Women / Social conditions; Algeria / Algiers; Drama; Feature films; Fiction films; DVD-Video